Social competences in German apprenticeship training within competence-based vocational education - Tschöpe, Tanja [Verfasser]; Dietzen, Agnes [Verfasser] (My University, 2019)
„This paper addresses social competences in vocational education and training (VET) and initial training since they form basic components of professional competence in most occupational sectors. From an empirical competence research approach in VET, it argues that there is a need for a clarification of the construct of social competences regarding its occupation-specific features. We present how to develop and validate such a model for the case of medical assistants. Based on empirical results for the measuring of social competences of medical assistants after three years of initial training, we recommend a further development of training for medical assistants with regard to certain dimensions of social competences.“ (authors' abstract; BIBB-Doku)
Keywords: L 1.1.2 Handlungs- und Lernfeldorientierung; G 1.2.3 Qualifikationsentwicklungen; S 6.4.5.2 Übrige Gesundheitsberufe (außer Ärzte und Apotheker); G 1.2.3.2 Anforderungen & Bedarfe; 370; Handlungskompetenz; Sozialkompetenz; Qualifikationsbedarf; Medizinischer Fachangestellter